Biodegradable composites with antibiotics and growth factors for dual release kinetics - Michael Seidenstuecker; Julian Hess; Anna Baghnavi; Hagen Schmal; Diana Voigt; Hermann O. Mayr (Journal of Materials Science: Materials in Medicine)
Abstract Bone infections are still a major problem in surgery. To avoid severe side effects of systemically administered antibiotics, local antibiotic therapy is increasingly being considered. Using a pressure-based method developed in our group, microporous β-TCP ceramics, which had previously been characterized, were loaded with 2% w/v alginate containing 50 mg/mL clindamycin and 10 µg/mL rhBMP-2. Release experiments were then carried out over 28 days with changes of liquid at defined times (1, 2, 3, 6, 9, 14, 21 and 28d). The released concentrations of clindamycin were determined by HPLC and those of rhBMP-2 by ELISA. Continuous release (anomalous transport) of clindamycin and uniform release (Fick’s diffusion) of BMP-2 were determined. The composites were biocompatible (live/dead, WST-I and LDH) and the released concentrations were all antimicrobially active against Staph. aureus. The results were very promising and clindamycin was detected in concentrations above the MIC as well as a constant rhBMP-2 release over the entire study period. Biocompatibility was also not impaired by either the antibiotic or the BMP-2. This promising approach can therefore be seen as an alternative to the common treatment with PMMA chains containing gentamycin, as the new composite is completely biodegradable and no second operation is necessary for removal or replacement. Graphical Abstract